Cladribine effects on patient-reported outcomes and their clinical and biometric correlates in highly active relapsing multiple sclerosis at first switch: the observational, multicenter, prospective, phase IV CLADFIT-MS study - Borriello, Giovanna; Chisari, Clara Grazia; Maimone, Davide; Mirabella, Massimiliano; Paolicelli, Damiano; Assogna, Francesco; Caradonna, Sandro; Patti, Francesco (Frontiers in Neurology, 2024)
Patient-reported outcomes (PROs) are essential for understanding the effects of MS and its treatments on patients' lives; they play an important role in multiple sclerosis (MS) research and practice. We present the protocol for an observational study to prospectively assess the effect of cladribine tablets on PROs and their correlation to disability and physical activity in adults with highly active relapsing MS switching from a first disease modifying drug (DMD) to cladribine tablets in routine clinical practice at study sites in Italy. The primary objective will be to evaluate changes from baseline in the impact of highly active MS on self-assessed physical functioning 52 weeks after the switch to cladribine tablets using the Multiple Sclerosis Impact Scale-29 (MSIS-29). Secondary objectives will include self-assessed psychological impact of highly active MS in daily life and general health after the switch to cladribine tablets as well as changes in cognitive function, anxiety, and depression symptoms. Additional PRO measures will include the Hospital Anxiety and Depression Scale (HADS), the EuroQoL 5-Dimension 5-Level (EQ-5D-5L), the Work Productivity and Activity Impairment Questionnaire: Multiple Sclerosis (WPAI:MS), and the Patient-Reported Outcomes Measurement Information System (PROMIS). Wearable devices will acquire activity data (step counts, walking speed, time asleep, and energy expenditure). Additional clinical, radiological, and laboratory data will be collected when available during routine management. The findings will complement data from controlled trials by providing insight from daily clinical practice into the effect of cladribine tablets on the patient’s experience and self-assessed impact of treatment on daily life.